ENHANCING VIRTUAL TEAM COHESION: ADDRESSING SOCIAL IDENTITY CHALLENGES - Andrew Ciganek (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study investigates the potential of Schön’s reflective practitioner approach to mitigate the negative attitudes and behaviors associated with team virtuality, specifically those stemming from a lack of shared group identity as explained by social identity theory. Virtual teams frequently struggle to develop cohesive group identities, which impedes team development and effective collaboration (Tajfel & Turner, 2004). Success in teams largely depends on strong interpersonal relationships (Bonebright, 2010). However, members frequently encounter difficulties in virtual settings from diminished social presence, feelings of loneliness and isolation, and fragile emotional bonds. (Zheng et al., 2024). Utilizing Schön’s reflective practitioner model (2016), this research explores how structured self-reflection and reflective practices can enhance team members’ awareness of group dynamics and improve perceptions of group identity. We hypothesize that reflective practices foster self-awareness and empathy, reducing the social distance often experienced in virtual teams. This study employs a mixed-methods approach to assess the impact of reflective practices on virtual team cohesion using longitudinal data over ten weeks from students in global virtual teams. Our findings underscore the significant potential of reflective practices in enhancing team virtuality outcomes, offering valuable insights for managing team identity in digital collaboration contexts.